An analytical study of the ethics of commitment to the administrative work of members of staffs to some the central Iraqi federations - Jawad, Sundus Mousa (International Journal of Psychosocial Rehabilitation, 2020)
One of the main goals of the research is administrative work and adherence to it, where the problem of research lies by answering some of the questions what is (the principles of ethics and commitment to administrative work) in sports federations in Baghdad and the research aims to prepare a scale (ethics and commitment to administrative work) and learn about its reality in sports federations In Baghdad, the researcher relied on the descriptive approach in the survey method appropriate to the nature of the research problem. The research sample was members of some sports federations in Baghdad.The researcher should pay attention to the members who possess characteristics and characteristics (to realize the principles of ethics and commitment to administrative work) to benefit from them in achieving the requirements and goals of higher departments and to reach the best results.